Type 2 Innate Lymphoid Cell (Ilc2)-Deficient Mice Are Transcriptionally Constrained During Nippostrongylus brasiliensis Infection - Damarius S. Fleming; Fang Liu; Joseph F. Urban; Robert W. Li (Pathogens)
Mouse models serve as a means of examining immune changes when genes of interest are knocked out (KO). One group of immune gene-producing cells that have been identified is type 2 innate lymphoid cells (Ilc2). These cells are involved in the production of Th2 equivalent immune responses and signal cytokine production during the resolution of Nippostrongylus brasiliensis parasite infection in mice lungs. However, many questions about Ilc2 activity in the gut remain. To study this, retinoic acid receptor (RAR)-related orphan receptor alpha (RORα)-deficient mice were infected with adult N. brasiliensis and arranged into four treatment groups. Ten days post-infection (dpi), mouse ileum tissue was extracted for RNA-Seq. The RORα-deficient mice showed little change in gene expression at 10 dpi (N = 51) when compared to the WT mice at 10 dpi (N = 915), displaying dysregulation within the mouse gut. Based on the results, the gene expression in the gut of Ilc2-deficient mice denoted that the inability to craft Ilc2 cells left the mice unable to mount classical helminth immune responses involving humoral, mast cell, and antibody Th2-driven reactions. Overall, the results showed the importance of Ilc2 in the gut during N. brasiliensis infections and the effect that the lack of these cells had on immunity.